2014
DOI: 10.1038/onc.2014.360
|View full text |Cite
|
Sign up to set email alerts
|

Serine–arginine protein kinase 1 (SRPK1) inhibition as a potential novel targeted therapeutic strategy in prostate cancer

Abstract: Angiogenesis is required for tumour growth and is induced principally by VEGF-A. VEGF-A pre-mRNA is alternatively spliced at the terminal exon to produce two families of isoforms, pro- and anti-angiogenic, only the former of which is upregulated in prostate cancer. In renal epithelial cells and colon cancer cells, the choice of VEGF splice isoforms is controlled by the splicing factor SRSF1, phosphorylated by SRPK1. Immunohistochemistry staining of human samples revealed a significant increase in SRPK1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
150
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 37 publications
0
150
1
4
Order By: Relevance
“…Interestingly, recent studies have identified pro-and anti-angiogenic VEGF splice forms (Bates et al 2002), which are differentially regulated in cancers, including in PCa (Woolard et al 2004, Mavrou et al 2014, and which (A) The VEGF promoter is regulated by a diverse array of transcription factors, hypoxia-inducible factors (HIFs), specificity protein-1 (Sp1), and most notably in the context of the present review, multiple nuclear receptors, including androgen (Eisermann et al 2013) and estrogen (Buteau-Lozano et al 2002, Dadiani et al 2009), which are indicated in red and yellow respectively. In addition, the VEGF promoter is regulated by progesterone (Wu et al 2004), vitamin D (Cardus et al 2009), and the liver-X nuclear receptors (LXR) (Walczak et al 2004).…”
Section: Transcriptional Regulation Of Pro-angiogenesis Pathways In Pcamentioning
confidence: 99%
“…Interestingly, recent studies have identified pro-and anti-angiogenic VEGF splice forms (Bates et al 2002), which are differentially regulated in cancers, including in PCa (Woolard et al 2004, Mavrou et al 2014, and which (A) The VEGF promoter is regulated by a diverse array of transcription factors, hypoxia-inducible factors (HIFs), specificity protein-1 (Sp1), and most notably in the context of the present review, multiple nuclear receptors, including androgen (Eisermann et al 2013) and estrogen (Buteau-Lozano et al 2002, Dadiani et al 2009), which are indicated in red and yellow respectively. In addition, the VEGF promoter is regulated by progesterone (Wu et al 2004), vitamin D (Cardus et al 2009), and the liver-X nuclear receptors (LXR) (Walczak et al 2004).…”
Section: Transcriptional Regulation Of Pro-angiogenesis Pathways In Pcamentioning
confidence: 99%
“…Another positive feedback mechanism between CD147 and insulin-like growth factor-1 (IGF-1) has been observed between cancerous and endothelial cells, and it also promotes the proliferation of tumor and vascular endothelial cells (Chen, Gou et al, 2012). Recent studies identified a key molecule in tumor cells, serinearginine protein kinase 1 (SRPK1), which is one main regulator of angiogenesis (Lucas et al, 2014;Brakspear et al, 2014;Brimacombe et al, 2014). SRPK1 can splice the pre-mRNA of vascular endothelial growth factor (VEGF) into pro-angiogenic mRNA.…”
Section: Interdependence Between Cancer Cells and Normal Cellsmentioning
confidence: 99%
“…However, it has been found in a screen to potently affect splicing of several genes involved in apoptosis and further-on to be able to decrease tumour growth in animal models [25] . Recently a class of small molecule compounds that inhibit SRPK1, a major regulator of AS through SR-protein phosphorylation, has been shown to inhibit VEGF splicing and angiogenesis in a model of ocular neovascularization [26] as well as melanoma xenografts growth [27] and orthotopic prostate cancer mouse models [28] . Potentially, other types of molecules could be involved in splicing modulation, like chemicals that affect splice factor/RNA interactions or molecules that affect directly the tertiary structure of a particular splice junction (Figure 1).…”
Section: Therapeutic Manipulation Of Splicingmentioning
confidence: 99%